A Structural Equation Modeling Approach to the Post-Slum Upgrading Policy Design: Empirical Evidence from Banjarbaru City, Indonesia - Akbar, Dhiya’ul; Rahman, Akbar; Radham, Iphan Fitrian; Mentayani, Ira (Engineering, Technology & Applied Science Research, 2026)
Slum settlements remain a persistent challenge in the urban areas of Banjarbaru City despite various upgrading programs implemented over the past decade. This study aims to evaluate the key variables influencing post-upgrading outcomes and develop a policy framework for sustainable slum improvement, focusing on the Kemuning area as a representative case. Using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach, the analysis identified three significant variables affecting post-upgrading environmental and social conditions: infrastructure quality (β = 0.408, p < 0.001), green open space management (β = 0.313, p < 0.001), and water, wastewater, and solid waste management (β = 0.321, p = 0.002). The findings demonstrate that adequate infrastructure, well-managed urban green spaces, and effective resource management systems significantly enhance both environmental quality and community well-being after the upgrading phase. This study contributes to the development of an evidence-based policy design for sustainable slum transformation in mid-sized tropical cities, emphasizing the integration of environmental, infrastructural, and social dimensions in post-slum governance.